Omrežje informacij na avtocestah - Šašek-Divjak, Mojca (Urbani izziv, 2000)
The article presents findings from a research concerning the contents framework, organisation and development of information - promotion centres along the high ways in Slovenia. The goal of the research was to present an adequate framework and content for a information - promotion network on the highways. Examples from abroad are shown, as well as proposals for designing information points on the highways, also for economic and touristic purposes.
Keywords: avtoceste; informacije; obcestne površine; promet; prostorsko urejanje; Slovenia; Slovenija; tourism; turistične informacije; turizem